In situ synthesis of a silicon flake/nitrogen-doped graphene-like carbon composite from organoclay for high-performance lithium-ion battery anodes. Issue 18 (11th February 2019) - Chen, Qingze; Zhu, Runliang; He, Qiuzhi; Liu, Shaohong; Wu, Dingcai; Fu, Haoyang; Du, Jing; Zhu, Jianxi; He, Hongping
Abstract : A silicon flake/nitrogen-doped graphene-like carbon composite with enhanced electrochemical performance was synthesized from organoclay via an in situ strategy. Abstract : A silicon flake/nitrogen-doped graphene-like carbon composite was prepared from organoclay via an in situ strategy, involving carbonization followed by low-temperature aluminothermic reduction. The pre-formed carbon sheets within the confined interlayer space of clay acted as nanotemplates for in situ synthesizing silicon flakes. As a lithium-ion battery anode, the composite exhibited excellent electrochemical properties.